1997
DOI: 10.1021/ma970615p
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Opening Polymerization of d,l-Lactide Using Rare-Earth μ-Oxo Isopropoxides as Initiator Systems

Abstract: Introduction.Polylactides are important biodegradable materials having biomedical, pharmaceutical, and environmental applications. [1][2][3][4][5] These polymers can be synthesized by ring-opening polymerization of lactides using anionic, cationic, or coordinated type initiators. [6][7][8][9][10] In order to obtain polymers with controlled characteristics (structure, molecular weight), initiators leading to a living type process are desirable. Ideally, they should also promote rapid polymerization.Anionic init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(47 citation statements)
references
References 19 publications
1
46
0
Order By: Relevance
“…Polylactones are of interest as biodegradable material for various medical applications. [1][2][3][4][5][6] The applications of new initiators, based on the lanthanide elements, has led to the production of several new macromolecular architectures like telechelic and block polymers incorporating poly(-caprolactone) (PCL) segments. [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Polylactones are of interest as biodegradable material for various medical applications. [1][2][3][4][5][6] The applications of new initiators, based on the lanthanide elements, has led to the production of several new macromolecular architectures like telechelic and block polymers incorporating poly(-caprolactone) (PCL) segments. [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…McLain et al have introduced the yttrium alkoxide Y(OCH 2 CH 2 NMe 2 ) 3 as a highly active initiator for the living ring-opening polymerization of L-lactide (L,Ldilactide) 3) . Subsequently, a series of other rare earth alkoxides such as Ln 5 (l 5 -O)(O i Pr) 13 (Ln = Y, La, Sm, Yb) have been studied and found to constitute a promising class of efficient initiators [4][5][6][7] . More recently we have found that the heterobimetallic yttrocene derivatives containing two linked amido-cyclopentadienyl ligands Li[Y(g 5 : g 1 -C 5 R 4 SiMe 2 NCH 2 CH 2 OMe) 2 ] (Scheme 1) are capable of efficiently polymerizing e-caprolactone.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 There is a great number of metal-based catalysts able to perform ROP reactions via coordination-insertion mechanism. However, some of these catalysts are toxic and difficult to remove from the reaction mixtures, preventing applications of the resulting polymers in biomedical and pharmaceutical areas.…”
Section: Introductionmentioning
confidence: 99%